Ecological Criteria in the Concept of Social-Ethical Marketing - Tamulienė, Vilma (Ekonomika, 2002)
The article analyses the problem of setting the ecological criterion in social-ethical marketing. The main levels of ecological evaluation are defined as essential elements of the social-ethical marketing concept, the criteria of ecological evaluation are highlighted in these levels and limits are set for the ecological evaluation in the context of corporate social responsibility.The determined criterion for the ecological evaluation in different levels in the context of social-ethical marketing becomes the target of practical argumentation.